Scaling laws for two-phase flow and heat transfer in high-temperature heat pipes. (15th June 2022) - Yilgor, Ilyas; Shi, Shanbin
Abstract: Heat pipes are high efficiency passive two-phase heat transfer devices utilizing the cyclical evaporation and condensation of a working fluid to transfer heat between two interfaces. High-temperature heat pipes are used in a variety of applications that require high operating temperatures such as nuclear microreactors, solar thermal reactors, furnaces, and aerospace systems. The high operating temperatures, and the reactivity of certain working fluids such as liquid metals, dictate stringent safety precautions and require high startup costs. The present work describes the scaling laws for two-phase flow and heat transfer in heat pipes and thermosyphons, that allows the use of low-temperature working fluids to study various phenomena in high-temperature heat pipes. Similarity parameters which were obtained from the non-dimensionalized governing equations and constitutive relations were tabulated and discussed. A case study involving the scaling of a microreactor heat pipe for the purpose of investigating the pressure and temperature profiles was given. In addition, a parametric study was conducted on the effects of the liquid and vapor Prandtl numbers on the steady state pressure and temperature profiles.